A Gro/TLE-NuRD corepressor complex facilitates Tbx20-dependent transcriptional repression - Kaltenbrun, Erin (2013)
The cardiac transcription factor Tbx20 has a critical role in the proper morphogenetic development of the vertebrate heart, and its misregulation has been implicated in human congenital heart disease. Although it is established that Tbx20 exerts its function in the embryonic heart through positive and negative regulation of distinct gene programs, it is unclear how Tbx20 mediates proper transcriptional regulation of its target genes. Here, using a combinatorial proteomic and bioinformatic approach, we present the first characterization of Tbx20 transcriptional protein complexes. We have systematically investigated Tbx20 protein-protein interactions by immunoaffinity purification of tagged Tbx20 followed by proteomic analysis using GeLC-MS/MS, gene ontology classification, and functional network analysis. We demonstrate that Tbx20 is associated with a chromatin remodeling network composed of TLE/Groucho co-repressors, members of the Nucleosome Remodeling and Deacetylase (NuRD) complex, the chromatin remodeling ATPases RUVBL1/RUVBL2, and the T-box repressor Tbx18. We determined that the interaction with TLE co-repressors is mediated via an eh1 binding motif in Tbx20. Moreover, we demonstrated that ablation of this motif results in a failure to properly assemble the repression network and disrupts Tbx20 function in vivo. Importantly, we validated Tbx20-TLE interactions in the mouse embryonic heart, and identified developmental genes regulated by Tbx20:TLE binding, thereby confirming a primary role for a Tbx20-TLE repressor complex in embryonic heart development. Together, these studies suggest a model in which Tbx20 associates with a Gro/TLE-NuRD repressor complex to prevent inappropriate gene activation within the forming heart.